Analisis Soft Skill Kesiapan Kerja Mahasiswa Tingkat Akhir Jurusan Pendidikan IPS - Visia Riyanita; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The problem in this research was final-year student’s employability soft skill of social education major. This study aims to provide a descriptive description of final-year student’s employability soft skill of social education major, Faculty of Teacher Training and Education, University of Lampung. The research method used in this research was descriptive quantitative. The research samples were taken from 20% of the population which is 192 students, it was using simple random sampling technique. Data collection techniques used in this research was employability scale. The result showed that 76% final-year students in social education major, Faculty of Teacher Training and Education, University of Lampung have medium level of employability. The result showed that final-year students in social education major, Faculty of Teacher Training and Education, University of Lampung have medium level of employability soft skills, consists of possitive self concept, self control, social skill, communication skill, dan high order thinking skill. The lowest of employability skills on final-year students majoring in social science education is self control. The highest of employability skills on final-year students majoring in social science education is possitive self concept.Pendidikan IPS Permasalahan  dalam  penelitian  ini  adalah  soft  skill  kesiapan  kerja  pada  mahasiswa  tingkat akhir Jurusan IPS. Penelitian ini bertujuan untuk memberikan gambaran deskriptif mengenai soft  skill  kesiapan  kerja  pada  mahasiswa  tingkat  akhir  Jurusan  IPS  FKIP  Universitas Lampung.  Metode  penelitian  yang  digunakan  pada  penelitian  ini  bersifat  deskriptif kuantitatif. Sampel penelitian  diambil dari 20% dari populasi yaitu  sebanyak 192 mahasiswa, sampel diambil dengan menggunakan teknik  simple random sampling. Teknik pengumpulan data  menggunakan  skala  kesiapan  kerja.  Hasil  penelitian  menunjukkan  bahwa  76% mahasiswa tingkat akhir jurusan pendidikan IPS FKIP Universitas Lampung memiliki tingkat kesiapan kerja yang sedang. Mahasiswa tingkat akhir Jurusan IPS FKIP Universitas Lampung memiliki tingkat soft skill kesiapan kerja yang sedang, yang terdiri dari possitive self concept, self control, social skill, communication skill, dan high order thinking skill. Soft skill kesiapan kerja  pada mahasiswa tingkat akhir jurusan pendidikan  IPS  yang rendah  yaitu  self control. Soft  skill  kesiapan  kerja  pada  mahasiswa  tingkat  akhir  jurusan  pendidikan  IPS  yang  tinggi yaitu possitive self concept.Kata kunci: bimbingan konseling, kesiapan kerja, soft skills, ips